Wetland Ecosystem Conflict: Implication for Agricultural Productivity and Food Security in Mbiabo, Odukpani, Cross River State, Nigeria. - Okpiliya, F. I; Ekong, A. E; Imoke, Eni (Mediterranean Journal of Social Sciences, 2013)
Conflict is a common daily occurrence in individuals, groups, communities and nation states. This study examined theconsequences of communal conflict of 2010 on peasant agricultural productivities in Mbiabo wetland of Odukpani LocalGovernment Area, Cross River State. The data for this was generated through questionnaire administration, participatory ruralappraisal and on the spot observation of the area. The population of farmers were drawn from six villages out of ten in the twocommunities. A total of 426 household heads form the sample size. The Likert scale which has the attributes Strongly Agreed(SA), Agree (A), Disagree (D), Undecided (U) and Strongly Disagree (SD) was used to analyse the causes of the conflict whilethe analysis of variance was used to test for the variation in crops productivity before and after the conflict in the area. At 0.05level of significance, the calculated value of 3.08 was greater than the table value of 2.23. This led to the rejection of the nullhypothesis, that there is no significant variation in agriculture productivity before and after the conflict and accepting thealternate one. The work revealed that conflict affected the utilization of wetland for farming thereby reducing the incomegenerated from farming and also reduced the quantity of crops harvested by approximately more than 50 per cent withoverriding influence on the quality of life of the people in the study area and the environs.